The Challenge of Change : Dealing with the Legacy of the Modern Movement. - Van den Heuvel, D. (IOS Press, 2008)
Conservation of architecture - and the conversation of modern architecture in particular - has assumed new challenges. Rather than attempting to return a modern building to its resumed original state, the challenge of these proceedings is to revalue the essence of the manifold manifestations of modern architecture and redefine its meanings in a rapidly changing world of digital revolution, worldwide mobility and environmental awareness. This volume aims to provide a variety of platforms for the exchange of ideas and experience. A large, international group of architects, historians, scholars,